NON-LINEAR MODEL IN REGION OF VERY LOW SPEEDS FOR A PERMANENT MAGNET DIRECT CURRENT MOTOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Thematic is in mechatronics and automation branches, applicable in the mobile robotics. Permanent Magnet DC collector motors, are widely used in small mobile robots due to their low-cost. Automated control systems of mobile robots, which operate under different conditions and require accuracy of operation, raise the need for the nonlinearities to be taken into account. In this article, a complex non-linear model of a PMDC motor with brushes is synthesized. The aim is to determine of suitable way of motor behaviour simulating in the region of very small speeds. The tribology aspects at different friction regimes are of great importance for a model at low speeds. The parameters and constants of the model are separately defined through referring to their physical equivalents. Besides the theoretical modelling, a simple mathematical way to determine the constants for this detailed model is deduced. Then the synthesized model is simulated and results are graphically represented and then compared with another similar model, proposed by another authors. As a conclusion, the advantages of this non-linear approach are revealed. This research is applicable as a study of direct-current motor and its simulation model or as facilitating example in lectures of robotics or control systems.